THE INFLUENCE OF ENDORSER CREDIBILITY AND ADVERTISING EFECTIVENESS TOWARDS BRAND ATTITUDE AND PURCHASE INTENTION OF OPPO INDONESIA - Veronica, Sharen; Prasastyo, Klemens Wedanaji (E-Jurnal Manajemen Trisakti School of Management (TSM), 2022)
The purpose of this study is to investigate the effect of endorser’s trustworthiness, expertness, similarity and attractiveness towards attitude to advert, the effect of attitude to advert to brand attitude and purchase intention, and lastly to analyze the moderating effect of brand attitude on the effect of attitude to advert to purchase intention on OPPO smartphone Indonesia in the case of millennials. There are four independent variables, one moderating variable and three dependent variables in this research. The independent variables are endorser’s trustworthiness, expertness, similarity and attractiveness, the moderating variable is brand attitude and the dependent variable is attitude to advert, brand attitude and purchase intention. Data used for this research is obtained from direct distribution questionnaires distributed in October through December 2018 through purposive sampling. Respondents belong in the millennial age group. All data collected from respondents is processed using Structural Equation Modeling method using WarpPLS software 6.0 edition. Confirmatory factor analysis were used in evaluating scale measures, whereas path coefficient and p value significance measures were used to assess the impact. Trustworthiness, expertness, similarity and attractiveness of an endorser was found to have a significant effect towards attitude to advert. Attitude to advert and brand attitude was found to have a highly significant effect to purchase intention. There was no moderating effect found between brand attitude and the effect of attitude toward advert to purchase intention. The findings provide understanding of consumer behavior in context of millennials toward the use of celebrity figure for endorsements in advertisements.